Comparative Analysis of Consumption Methods and Minimum Maximum Stock Level (MMSL) in Improving the Efficiency and Effectiveness Inventory of Antibiotic Drugs at Aisyiyah Hospital Bojonegoro - Wijayanto, Pramono Apriawan; Sriatmi, Ayun; Jati, Sutopo Patria (Universitas Aisyah Pringsewu, 2021)
Antibiotic spending at the Aisyiyah Hospital Pharmacy Installation showed a value of IDR 6,045,618,320.00 in 2018 increased to IDR 5,043,476,179.00 in 2019, and there were still often vacancies and excess stock. This study aimed to compare the efficiency and effectiveness parameters of planning consumption methods with simulation results using the Minimum-Maximum Stock Level (MMSL) method for antibiotic drug types. Study samples were 17 types of antibiotic drugs category A obtained from ABC analysis, the inclusion criteria of drugs with high cost, high volume, and clinically important drugs, and the exclusion criteria were drugs with unstable supply. The results showed that there were significant differences in inventory value, ITOR, death stock, and stock out when controlling drug supplies by applying the MMSL method. The inventory value when applying the MMSL method decreased to IDR 503,938.00 with a p-value of 0.000 less than 0.05, while the ITOR value increased to 32.40 with a p-value = 0.030 less than 0.05, the number of death stocks decreased to 97 items of antibiotics with a p-value of 0.048 less than 0.05, while the value of stock-outs is empty or zero stock out with a value of p = 0.004 less than 0.05. Aisyiyah Hospital, Bojonegoro, should carry out the process of antibiotic drugs planning by applying an integrated Management Information System (MIS) so that the data on supplies use and stock is accurate.Nilai belanja antibiotik di IFRS Aisyiyah Bojonegoro menunjukkan sebesar Rp. 6.045.618.320,00 (2018) meningkat menjadi sebesar Rp. 5.043.476.179,00 (2019), dan masih sering terjadi kekosongan stok dan stok yang berlebih. Penelitian ini bertujuan membandingkan parameter efisiensi dan efektivitas perencanaan metode konsumsi dengan hasil simulasi menggunakan metode Minimum-Maximum Stock Level (MMSL) untuk jenis obat antibiotika. Sampel penelitian adalah 17 jenis obat antibiotika kategori A hasil analisa ABC, dengan kriteria inklusi adalah obat high cost, high volume, clinically important drug, serta kriteria eksklusi adalah obat dengan pasokan yang tidak stabil. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan pada nilai persediaan, ITOR, death stock, dan stock out saat pengendalian persediaan obat dengan menerapkan metode kosumsi dengan metode MMSL. Nilai persediaan saat menerapkan metode metode MMSL menurun sebesar Rp. 503.938,00 dengan nilai p = 0,000 kurang dari 0,05, nilai ITOR meningkat mencapai 32,40 dengan nilai p = 0,030 kurang dari 0,05, jumlah death stock mengalami penurunan menjadi 97 item antibiotik dengan nilai p = 0,048 kurang dari 0,05, serta nilai stock out adalah kosong atau nol stock out dengan nilai p = 0,004 kurang dari 0,05. Rumah Sakit Aisyiyah Bojonegoro perlu melaksanakan proses perencanaan antibiotik melalui Sistem Informasi Manajemen (SIM) yang terintegrasi agar data pemakaian dan stok persediaan akurat.